Sport resumption and quality of life after surgical correction of anomalous origin of a coronary artery from the opposite sinus - André, Camille-Océane; Hodzic, Amir; Dolladille, Charles; Maragnes, Pascale; Cousergue, Cynthia; Ollitrault, Pierre; Sayegh, Jimmy; Belli, Emré; Labombarda, Fabien (Frontiers in Cardiovascular Medicine, 2023)
Objectives We sought to assess the resumption of sport, exercise performances, and quality of life (QoL) in adults and children after surgical repair of anomalous coronary arteries originating from the opposite sinus (ACAOS). Materials and methods Patients who underwent surgical repair for ACAOS between 2002 and 2022 were retrospectively identified. Information about sports activity and exercise performance based on metabolic equivalents of task (METs) calculated at the last exercise stress test, were collected. QoL was assessed using age-appropriate questionnaires (Paediatric QoL Inventory, cardiac module version 3.0 for patients < 18 years; SF-36 QoL Inventory for adults). Patients’ METS and patients’ QoL-scores were compared to reference population using the Wilcoxon test. Results 45 patients were enrolled (males 71%, adults 49 %, anomalous right coronary 84%). Median age at surgery was 15 years; median follow-up after surgery was 2.3 years [4 months - 12 years]. All post-operative exercise stress tests were normal, METs and VO2 max patients’ values did not differ from healthy children or adults (Exercise intensity: 12.5 ± 4.7 vs 13.4 ± 2 METS, p = 0.3 ; VO2 max: 43.6 ± 16.6 vs 46.9 ± 7 ml/kg/min, p = 0.37). For adults, QoL- scores were similar between ACAOS patients and controls. For children, there was no significant difference between the study patients’ scores and those of the reference population, except for physical appearance proxy-report (p = 0.02). Conclusion In our study, the practice of sports, exercise stress testing and QoL were not adversely affected after ACAOS repair.